Influence of intrauterine growth status on aortic intima-media thickness and aortic diameter in near-term fetuses: a comparative cross-sectional study. (15th April 2022) - Akhter, Zohaib; Nuruddin, Rozina; Azam, Iqbal; Malik, Ayesha; Mohammed, Nuruddin
Abstract: Intrauterine undernutrition may lead to fetal vascular programming. We compared abdominal aortic intima-media thickness (aIMT) and aortic diameter (aD) between appropriate for gestational age (AGA) and growth-restricted fetuses (GRF). We recruited 136 singleton fetuses at 34–37 weeks of gestation from Fetal Medicine Unit of Aga Khan University Hospital, Karachi (January–November 2017). Subjects were classified as AGA ( n = 102) and GRF ( n = 34) using INTER-GROWTH 21st growth reference and standard ultrasound protocol. Their far- and near-wall aIMT and aD were compared after adjustment of maternal age, first-trimester body mass index, fetal gender, hypertension and hyperglycemia in pregnancy. As the severity of growth restriction increased in GRF, aIMT and aD showed an increasing and a decreasing trend, respectively. Both far- and near-wall aIMT in GRF [(adj. β = 0.082, 95% confidence interval [CI] 0.042–0.123) and (adj. β = 0.049, 95% CI 0.010–0.089)] were significantly greater with reference to AGA fetuses. GRF subgroup analysis into small for gestational age (SGA) fetuses and intrauterine growth restricted (IUGR) revealed highly significant difference between AGA and IUGR for far (0.142 mm, P -value < 0.001) and near-wall aIMT (0.115 mm, P -value < 0.001) and marginally significant aD difference (0.51 mm, P -value 0.05). These findings suggest that the extent of fetal aortic remodelling is influenced by the severity of growth restriction. Hence, the targeted interventions for the cardiovascular health promotion of IUGR and SGA born neonates are desirable during early childhood, particularly in set ups with high prevalence of low birth weight babies.